Study of congenital talipes equinovarus cases and its radiological correlation - Prabahita Baruah; Pradipta Ray Choudhury; K L Talukdar (Wolters Kluwer Medknow Publications, 2013)
Background and aims : congenital talipes equinovarus (CTEV) or club foot is one of the most common congenital orthopaedic anomalies and is increasing day by day with the growing millions of this country. However, it still continues to challenge the skills of the surgeons as it has a notorious tendency to relapse. Part of the reason behind its relapse is the failure to recognize the underlying pathoanatomy. Again the controversy regarding the radiographic parameter which best represents the deformity of club foot still continues. However, the talocalcaneal angle in both AP (anterior- posterior) and lateral view is considered as the best parameter to diagnose a case of CTEV radio graphically. The aim of the study is to study the cases of CTEV and their radiological correlation. Materials and methods : Sixty cases of CTEV attending the orthopaedic OPD, Gauhati Medical College were taken for study. Clinical history, photographs and radiographs (X-rays) of these cases were taken. Results and observations: out of 60,63.3% cases were male, 43.3% cases were bilateral, 36.04% cases showed the talocalcaneal angle (AP view) ranging 260 - 300. Conclusion : The talocalcaneal angles, in both, AP (anterior-posterior) and a lateral view, in a normal foot is more than 35 degrees, but in CTEV these are reduced. Functional anatomy of CTEV is a prerequisite for achieving an aligned and supple foot with a good prognostic value.